Peningkatan Kemampuan Berhitung Melalui Permainan Wortel Pintar - Yullianti, Ria; Ismet, Syahrul (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research aims to improve the numeracy skills of children aged 4-5 years at POS PAUD Ananda, Kota Sawahlunto through the educational game Carrot Pintar. The research method used is Classroom Action Research (PTK) which is carried out in two cycles, each consisting of planning, action, observation and reflection stages. The results of the research show that the Smart Carrot game is effective in improving numeracy skills, which can be seen from the increase in children's average success scores from initial conditions to cycle II. Thus, the Smart Carrot game can be used as an interesting and interactive alternative learning media to improve the numeracy skills of young children.